PENERAPAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTION UNTUK MENINGKATKAN ANTUSIASME DAN PRESTASI BELAJAR - Yonesrizal (DIADIK, 2024)
The purpose of this research is to describe the application of explicit instruction learning model and the effectiveness of explicit instruction learning model to improve enthusiasm and learning achievement at IPA subject of the fourth year class in SD Negeri 01 Lubuk Pinang Mukomuko Regency. The research subjects are the students of the fourth year class SDN 01 Lubuk Pinang at the first semester of the academic year 2022/2023 which is 21 students in class IV A become classroom action research class, 21 students in class IV B become experiment class, and 22 students in class IV C becomes control class. The research design used is classroom action research and quasi experiment. The data collection techniques used are teacher’s observation sheet in applying explicit instruction learning model, student’s enthusiasm observation sheet, and learning result test. The analysis of data uses average scores and test tested that is consists of difference by cycle tested and difference two samples tested that is not related . The research result shows that application of explicit instruction can increase enthusiasm and student’s learning achievement as well as effective in increasing student’s learning result of fourth year class in SD Negeri 01 Lubuk Pinang Mukomuko regency.